2023
DOI: 10.1021/acs.jafc.3c03881
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Ketoacyl-CoA Synthase 10 (KCS10) Homologue from Alfalfa Enhances Drought Tolerance by Regulating Cuticular Wax Biosynthesis

Yafang Wang,
Yushi Liu,
Xinya Pan
et al.

Abstract: Cuticular wax, forming the first line of defense against adverse environmental stresses, comprises very long-chain fatty acids (VLCFAs) and their derivatives. 3-Ketoacyl-CoA synthase (KCS) is a rate-limiting enzyme for VLCFA biosynthesis. In this study, we isolated KCS10, a KCS gene from alfalfa, and analyzed the effect of gene expression on wax production and drought stress in transgenic plants. MsKCS10 overexpression increased compact platelet-like crystal deposition and promoted primary alcohol biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies have identified these enzymes in multiple plant species. For example, overexpression of MsKCS10 promoted the accumulation of cuticular wax in alfalfa leaves and enhanced drought resistance [57]. Additionally, another report revealed that three CER2 proteins participating in FAE played a crucial role in VLCFA synthesis, especially for the carbon chain above C 28 [58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified these enzymes in multiple plant species. For example, overexpression of MsKCS10 promoted the accumulation of cuticular wax in alfalfa leaves and enhanced drought resistance [57]. Additionally, another report revealed that three CER2 proteins participating in FAE played a crucial role in VLCFA synthesis, especially for the carbon chain above C 28 [58].…”
Section: Discussionmentioning
confidence: 99%